2020
DOI: 10.1371/journal.pone.0231234
|View full text |Cite
|
Sign up to set email alerts
|

The evolving systemic biomarker milieu in obese ZSF1 rat model of human cardiometabolic syndrome: Characterization of the model and cardioprotective effect of GDF15

Abstract: Cardiometabolic syndrome has become a global health issue. Heart failure is a common comorbidity of cardiometabolic syndrome. Successful drug development to prevent cardiometabolic syndrome and associated comorbidities requires preclinical models predictive of human conditions. To characterize the heart failure component of cardiometabolic syndrome, cardiometabolic, metabolic, and renal biomarkers were evaluated in lean and obese ZSF1 19-to 32-week-old male rats. Histopathological assessment of kidneys and hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In male C57/BL6J mice, Calligaris et al reported that feeding with an HFD for 16 months was required to develop substantial cardiac fibrosis and hypertrophy [45]. In addition, 20-week-old obese Zucker diabetic fatty/spontaneously hypertensive heart failure F1 hybrid (ZSF1) male rats showed important alterations in major systemic biomarkers of cardiovascular function without histopathological modifications in the heart [46].…”
Section: Discussionmentioning
confidence: 99%
“…In male C57/BL6J mice, Calligaris et al reported that feeding with an HFD for 16 months was required to develop substantial cardiac fibrosis and hypertrophy [45]. In addition, 20-week-old obese Zucker diabetic fatty/spontaneously hypertensive heart failure F1 hybrid (ZSF1) male rats showed important alterations in major systemic biomarkers of cardiovascular function without histopathological modifications in the heart [46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GDF15 was protective of β-cells, and administration of GDF15 prevented diabetes onset in mice ( 34 ). In addition, 12 weeks of GDF15 treatment improved exercise capacity in obese ZSF1 rats ( 35 ). Collectively, these reports indicate that skeletal muscle GDF15 may synergistically enhance β-cell function.…”
Section: Introductionmentioning
confidence: 99%
“…In aged obese ZSF1 rats with advanced renal disease, chronic treatment with 2-methoxyestradiol and its structural analog 2-ethoxyestradiol downregulated renal VEGF expression and provided renal protection [ 70 ]. Treatment with growth differentiation factor 15 decreased body weight, food intake, blood glucose, and triglycerides and improved exercise capacity in obese ZSF1 males while decreasing VEGF [ 71 ]. VEGF is a marker of vascular injury and inflammation, and as such may not be directly responsible for ZSF1 comorbidities but may help monitor disease progression and correction by therapeutic agents [ 24 ].…”
Section: Discussionmentioning
confidence: 99%